The Influence of Brand Image and Product Quality to Converse Shoe Purchasing Decisions (Study on UPN "Veteran" East Java Students) - Mahendra Alfatoni Hadinata; Ugy Soebiantoro; Egan Evanzha Yudha Amriel (International Journal of Economics (IJEC), 2023)
This study aims to determine the effect of brand image on the decision to purchase Converse shoes for the study of UPN "Veteran" East Java students and the effect of product quality on the purchase decision for Converse shoes for the study of UPN "Veteran" students in East Java. The population in this study was East Java UPN "veteran" students. The sample in this study used the Likert formula and found the results of 100 respondents. The method used in this study uses the GForm form. The analysis technique in this study uses PLS (Partial Least Square). The results of this study indicate that the indicator Brand Image variable that has the highest percentage is Converse product details in line with expectations (X1.2) while the Product Quality the indicator variable that has the highest percentage is Converse shoes more attractive than other shoe brands (X2.3). Comparison quality product from brands competitor Shoe Converse done student push student do Buying decision.